2012
DOI: 10.3325/cmj.2012.53.450
|View full text |Cite
|
Sign up to set email alerts
|

Relations of the Big-Five personality dimensions to autodestructive behavior in clinical and non-clinical adolescent populations

Abstract: AimTo examine the relationship between the Big-Five personality model and autodestructive behavior symptoms, namely Autodestructiveness and Suicidal Depression in two groups of participants: clinical and non-clinical adolescents.MethodsTwo groups of participants, clinical (adolescents with diagnosis of psychiatric disorder based on clinical impression and according to valid diagnostic criteria, N = 92) and non-clinical (high-school students, N = 87), completed two sets of questionnaires: the Autodestructivenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Additionally, we found that NSSI frequency was positively correlated with neuroticism and depression and negatively correlated with extraversion, agreeableness and conscientiousness. These findings were also consistent with those of earlier studies (Claes et al, 2014;Goldstein et al, 2009;Hasking et al, 2010;Robertson et al, 2013;Topić et al, 2012).…”
Section: Self-injurerssupporting
confidence: 94%
See 1 more Smart Citation
“…Additionally, we found that NSSI frequency was positively correlated with neuroticism and depression and negatively correlated with extraversion, agreeableness and conscientiousness. These findings were also consistent with those of earlier studies (Claes et al, 2014;Goldstein et al, 2009;Hasking et al, 2010;Robertson et al, 2013;Topić et al, 2012).…”
Section: Self-injurerssupporting
confidence: 94%
“…Research showed that NSSI frequency was positively associated with neuroticism (some studies examined negative affectivity and emotional instability, which are similar constructs as neuroticism; Claes et al, 2014;Goldstein, Flett, Wekerle, & Wall, 2009;Topić, Kovačević, & Mlačić, 2012), and negatively associated with extraversion (Hasking et al, 2010;Topić et al, 2012), agreeableness (Hasking et al, 2010;Robertson, Miskey, Mitchell, & Nelson-Gray, 2013), and conscientiousness (Hasking et al, 2010;Topić et al, 2012). Additionally, one study reported a positive correlation between openness and NSSI (Goldstein et al, 2009), one study reported a negative correlation (Hasking et al, 2010), and the others reviewed above reported a non-significant correlation between openness and NSSI.…”
Section: Introductionmentioning
confidence: 79%
“…Studies 1–3 included the following measures of suicide risk and protective factors: depressive symptoms, Center for Epidemiologic Studies-Depression scale (CES-D, Study 1) [ 80 ], CES-D 10 (Study 2) [ 81 ], Depression Anxiety and Stress Scales (DASS, Study 3) [ 82 ]; stress and anxiety (DASS, Study 3); a 5-item version of the Beck Hopelessness Scale (BHS5) [ 83 ]; a 5-item version of the UCLA Loneliness Scale (UCLA5) [ 84 ]; the Multidimensional Scale of Perceived Social Support (MSPSS, Studies 1–3) [ 85 ]; and satisfaction with life (SWL, Study 3) [ 86 ]. We included weekly hours of online shopping (Study 2) [ 66 ], and the International Personality Item Pool (IPIP) Intellect scale (Study 3) [ 87 ], as discriminant validity checks [ 88 ]. All measures demonstrated adequate internal reliability (α ≥ .80).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have reported an association between personality dimensions and a wide range of mental problems. Lower emotional stability is associated with anxiety, depression and other negative emotions [ 11 , 12 , 13 , 14 , 15 , 16 ], while higher extroversion protects against depressive symptoms [ 16 , 17 ]. Circadian preference has been considered a potential intervening factor in affective and other minor psychiatric disorders [ 18 ] and chronotype has been found to correlate with some personality dimensions [ 19 ].…”
Section: Introductionmentioning
confidence: 99%